If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12y+3=9y-5
We move all terms to the left:
12y+3-(9y-5)=0
We get rid of parentheses
12y-9y+5+3=0
We add all the numbers together, and all the variables
3y+8=0
We move all terms containing y to the left, all other terms to the right
3y=-8
y=-8/3
y=-2+2/3
| 10^x=3.65 | | |7x+5|+11=3 | | (750000/x)+.5x=500000 | | 2•m=2•(1/2) | | 4+x+x=34 | | 8x+24=125 | | 2x2+12x+68=0 | | 0-(-3y-7y)=0 | | 2/5a-5+8/9a=19 | | x²+x+2.5=0 | | |2x+6-5x|=9 | | -2b+2(b+-10)=2(10+5b) | | c(c/2)+c^2=5c^2-7c(c/2) | | (a−2)×12=0.33 | | 13(10+y)-12=43-5(y+3) | | 4x-3/5=6-2x/2 | | 8r+25=5R | | 2/x+4=1/x-2 | | 2√x+4=1√x-2 | | 10=-2.7t^2+40t+6.5 | | 1.5x+24=3x | | .15c=600 | | 126=-21x | | -136=-17x | | 440=15x | | 17=k/14 | | (x/4)3=0.5 | | 8^x=2^x+2 | | 8^x=2^x+@2 | | 8^x=2^x+@ | | 8(x+10)+21x=12(x+5)-(16+x) | | -4(-5v+5)-4v=6(v-4)-1 |